Maintenance of large subpopulations of differentiated CD8 T-cells two years after cytomegalovirus infection in Gambian infants. - David J C Miles; Marianne van der Sande; David Jeffries; Steve Kaye; Olubukola Ojuola; Mariama Sanneh; Momodou Cox; Melba S Palmero; Ebrima S Touray; Pauline Waight; Sarah Rowland-Jones; Hilton Whittle; et al. (PLoS ONE, 2008)
In a previously published study, we found that large differentiated subpopulations of CD8 T-cells emerged rapidly after CMV infection in young infants and persisted throughout the following year. Here we describe a follow-up study conducted on the same infants to establish whether the differentiated subpopulations continued through the second year post-infection.CMV-specific cells identified using tetramers remained more activated and differentiated than the overall CD8 population. The large subpopulation of differentiated cytotoxic (CD28(-)CD62L(-)Bcl-2(low)CD95(+)perforin(+)) cells that emerged rapidly after infection remained stable after two years. No similar subpopulation was found in CMV-uninfected infants indicating that two years after infection, CMV remained a major factor in driving CD8 T-cell differentiation. Although markers of activation (CD45R0 and HLA-D) declined throughout the first year, HLA-D expression continued to decline during the second year and CD45R0 expression increased slightly. The age-related increase in IFNgamma response observed during the first year continued but was non-significant during the second year, indicating that the rate of functional improvement had slowed substantially. CONCLUSIONS / SIGNIFICANCE: The large differentiated subpopulations of CD8 T-cells that had emerged immediately after CMV infection persisted through the second year post-infection, while levels of activation and functional capacity remained fairly constant.